How is real convergence driving nominal convergence in the new EU Member States? - Sarah M. Lein-Rupprecht; Miguel A. León-Ledesma; Carolin Nerlich (European Central Bank (ECB), 2007)
The purpose of this paper is to evaluate the empirical relevance of real convergence on the process of nominal convergence for the new EU Member States. We discuss two of the main channels through which real convergence could affect relative prices with respect to the euro area: productivity growth and increased trade openness. Productivity growth can have a positive effect on price levels via the Balassa-Samuelson effect, whereas increased openness leads to reductions in mark-ups and costs and therefore can have a negative impact on prices. In order to assess their empirical relevance, we used a Structural VAR model to which we applied a model reduction algorithm. This method accounts for endogeneity and simultaneity and circumvents the problem of limited data availability. Our findings show that, in general, openness has had a negative impact and productivity growth a positive one on price level convergence with respect to the euro area.
Keywords: O52; E31; 330; inflation; new EU Member States; nominal convergence; real convergence; Wirtschaftliche Konvergenz; Produktivität; Handelsliberalisierung; Inflation; Geldpolitische Transmission; EU-Mitgliedschaft; EU-Staaten